Students’ Perceptions toward Lecturer’s Strategies in Teaching Listening during Pandemic of Covid-19 - Yulan M. Puluhulawa; Ana Mariana; Dahlia Husain (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
The aim of this research was to find out the students’ perceptions toward the lecturers’ strategies in teaching listening during pandemic of Covid-19. The research was conducted at English Literature Study Program, Faculty of Social Sciences, Muhammadiyah University of Gorontalo. There were 26 participants in this research who enrolled listening subject. This research used qualitative method and the data were collected by using questionnaire that was designed in Google Form which accomodates 2 aspects, materials and learning activities. The result of the research showed that most of students find difficulties in learning listening through online learning because they do not have high-speed internet to access the material. So, it affected the quality of listening audio-audiovisual because the materials were fully online accessed. But, the students also showed positive and well-motivated attitude during online learning in Listening Subject. Most of students revealed that the materials that the lecturer provided during the process of teaching and learning can significantly improve their understanding to the content of listening materials and also improve their listening skill.